Can elevated lactate and LDH produce a false positive enzymatic ethanol result in live patients presenting to the emergency department?. (4th March 2018) - Nacca, Nicholas; Hodgman, Michael J.; Lao, Kirselle; Elkins, Matthew; Holland, Michael G.
Abstract: Background: There have been allegations in the courtroom that elevated serum lactic acid in trauma victims can yield a falsely elevated serum ethanol assay. Most hospitals utilize an indirect method of ethanol measurement where a serum sample is added to a mix of alcohol dehydrogenase and oxidized nicotinamide adenine dinucleotide (NAD+). This allows any ethanol in the patient's serum to be metabolized to acetaldehyde, and in the process results in the reduction of NAD + to NADH. NADH is then measured using spectrophotometry. The courtroom allegation stems from the concept that oxidation of lactate to pyruvate by lactate dehydrogenase (LDH) results in the same molar-for-molar reduction of NAD + to NADH, and could therefore theoretically cause patients with elevated lactate and LDH to have a falsely elevated ethanol concentration. Methods: Patients with elevated lactic acid and LDH concentrations who presented to a university hospital from 20 April 2015 to 13 December 2015 were identified to provide possible test specimens. If a sufficient amount of serum was available, the sample was used to re-run the lactate and LDH concentration simultaneously with an enzymatic ethanol assay. Any samples that had elevated lactic acid and LDH concentrations on this retesting, and also yielded a positive ethanol concentration, were sent for confirmatory gas chromatography testing of ethanol concentrations. A control group of 20 samples with normal lactate and LDH were included. Results: A total of 37 samples were included in the final analysis. Only 4 patients had an elevated enzymatic ethanol concentration, and all 4 also had a measurable GC ethanol concentration. The lactate in this dataset ranged from 2.4 to 24.2 mmol/L, with a mean of 6.53 mmol/L (normal value 0.5–2.2). The LDH ranged from 242 to 8838 U/L with a mean of 1695 U/L (normal value 122–225 U/L). Twenty control samples were run on patients with normal lactate and LDH, none of which yielded a positive enzymatic ethanol result. Conclusions: This data does not support the contention that an elevated LDH and lactate can yield a false positive serum ethanol result as run by enzymatic ethanol assay in live patients presenting to the emergency department.